2019
DOI: 10.1038/s41598-019-53961-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of TiO2-FeO-Na2O slag viscosity through molecular dynamics simulations for an energy efficient ilmenite smelting process

Abstract: Along with the increasing demand for the TiO2 pigment, the ilmenite smelting process has also become significant because it can utilize both rock- and sand-type ilmenite. However, due to the high liquidus temperature of the TiO2 slag system, the smelting process is highly energy consuming. In the present study, the viscosity of molten ilmenite slag was estimated using molecular dynamic simulations at a high temperature to achieve an appropriate and efficient slag design. To verify the validity of the simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…They also calculated the coordination number (CN) of titanium using molecular dynamic (MD) simulations, by which the CN of Ti in the TiO 2 -rich melts would be 6, i.e., the [TiO 6 ]-octahedron is main backbone structure of the melts 28,29 . The MD simulation and viscosity measurements were also performed by Kim and Park for the FeO-TiO 2 (-Na 2 O) systems 30 . They obtained the similar results with Hu et al 28 and Huang et al 29 for the FeO-TiO 2 system and additionally found that Na 2 O decreases the viscosity of the melts, resulting from a decrease in CN of titanium by Na 2 O addition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also calculated the coordination number (CN) of titanium using molecular dynamic (MD) simulations, by which the CN of Ti in the TiO 2 -rich melts would be 6, i.e., the [TiO 6 ]-octahedron is main backbone structure of the melts 28,29 . The MD simulation and viscosity measurements were also performed by Kim and Park for the FeO-TiO 2 (-Na 2 O) systems 30 . They obtained the similar results with Hu et al 28 and Huang et al 29 for the FeO-TiO 2 system and additionally found that Na 2 O decreases the viscosity of the melts, resulting from a decrease in CN of titanium by Na 2 O addition.…”
Section: Resultsmentioning
confidence: 99%
“…They obtained the similar results with Hu et al 28 and Huang et al 29 for the FeO-TiO 2 system and additionally found that Na 2 O decreases the viscosity of the melts, resulting from a decrease in CN of titanium by Na 2 O addition. A decrease in CN of titanium means the network breaking event by Na 2 O, resulting in a decrease in viscosity 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The operation of high temperature pyrometallurgical processes nearly always involves the formation of chemically aggressive liquid phases (i.e., slag, matte, speiss, liquid metal, molten salts, etc). In specific cases such as ilmenite reduction in an electrical arc furnace, the liquid phase is so aggressive that the only option to contain it is by freezing it on the surface of the vessel using, for example, water-cooled copper plates [41]. Hence, the optimal selection of lining materials of high-temperature pyrometallurgical reactors is a critical task to limit shutdowns and prevent catastrophic accidents.…”
Section: Refractory Crucible Selection For High Temperature Applicationsmentioning
confidence: 99%
“…According to the Eyring equation, Kondratiev explored a quasi-chemical viscosity model by defining the “structure units of viscous flow”. In addition to the above theoretical models, there are some empirical or semiempirical formulas for viscosity estimation in terms of the relationship of composition and viscosity, , and some scholars also estimate the melt viscosity through molecular dynamics simulation. , …”
Section: Introductionmentioning
confidence: 99%